Scripture characters v.4 - Robinson, Thomas (London : Printed for Gale and Fenner, 1815)
This text, Scripture Characters, is otherwise known as: A practical improvement of the principal histories in the Old and New Testament. Made up of multiple volumes this is volume four of four. Written by Thomas Robinson, an M.A. Vicar of St. Mary's, Leicester ; and late Fellow of Trinity College, Cambridge.
Scripture characters ; or, A practical improvement of the principal histories in the Old and New Testament. In four volumes / by Thomas Robinson, M.A. Vicar of St. mary's, Liecester ; and late Fellow of Trinity College, Cambridge.
Slight foxing and damages to the inner pages, with staining and slight crumbling of the front and back cover. The ninth edition; containing a biographical account of the author. Some additional publisher info: manufactured by: London: Cornish and Co.
Keywords: Rare books, scripture characters, Thomas Robinson, Fellow of Trinity College, Cambridge.